Pain Perception in Taekwondo: Relationship to Injury, Experience, and Time Loss - Zhao, Renee T.; Kandil, Abdullah; Nguyen, Danh V.; Campos, Luis; Amin, Nirav H.; Chang, Eric Y. (Sports Medicine International Open, 2020)
While the majority of sports medicine literature discusses the incidence and rehabilitation of sports injuries, there is a paucity regarding an athlete’s perception of pain during these injuries. This study describes the relationship between the perception of pain from injuries in a Taekwondo collegiate conference and injury characteristics such as injury type, location, mechanism, time loss, and the athlete’s competitive experience. In our study, we obtained reports from 62 Taekwondo athletes who were injured during the 2008–2009 Pacific West Taekwondo Conference collegiate season. Pain was recorded using the Numeric Rating Scale for Pain during athletes’ acute injury and at two weeks, six weeks, and subsequent monthly follow-ups. Pain scores were highest for sprain/strains (mean 5.4, standard error 0.47) and injuries to the lower body (mean 5.6, standard error 0.36). By mechanism, falls (mean 5.8, standard error 0.67) reported the highest levels of pain. There was a significant positive association between pain and time loss, where an increase in pain score of 1 point was associated with about 0.85 days (standard error 0.37) of time lost from training (p=0.0284). Notably, head injuries, although potentially more devastating and attracting widespread concern, were considered less painful.
Keywords: Sports Injury Rates; Acute Pain; Martial Arts; Return to Play